Penguatan Nilai Entrepreneurship Dalam Membentuk Karakter Mandiri Di Tengah Pandemi Covid-19 (Studi Deskriptif Pada Mahasiswa FKIP Universitas Khairun) - Sitirahia Hi. Umar; Wahyudin Noe (Jurnal Rontal Keilmuan Pancasila dan Kewarganegaraan, 2021)
The Covid-19 pandemic that hit the country is a serious concern for the government in raising the economy of the community, including students. One of the efforts made by the government is by holding the Indonesian Student Entrepreneurship Program (PKMI) as a form of implementation of the Independent Learning-Independent Campus (MBKM) policy. The purpose of the program is to provide broad opportunities for students to be involved in entrepreneurial activities so that they hope to form an independent character. However, this is not appreciated because of the low interest of students to be involved in entrepreneurial activities as happened to the students of the Faculty of Teacher Training and Education, Khairun University. This problem must be a joint concern of the educators/lecturers and the leadership of the Khairun University higher education institution. In general, this study aims to obtain descriptive information about the extent to which the internalization of entrepreneurship values in the formation of independent character of Khairun University FKIP students. This research approach is qualitative by using descriptive study method. The results illustrate that: 1) Khairun University FKIP students' understanding of entrepreneurship in general is relatively low 2) the process of internalizing the value of entrepreneurship in the formation of students' independent character is carried out through various educational channels 3) supporting factors in internalizing the value of entrepreneurship to students.